Audit Sistem dan Evaluasi Tata Kelola menggunakan Framework COBIT 4.1 pada UPT Komputer STT Terpadu Nurul Fikri - Muhammad Habib; Suhendi Suhendi (Jurnal Informatika Terpadu, 2020)
IT Governance, or in the Indonesian language, means Tata Kelola Teknologi Informasi is an integrated part of covering organizational leadership management, structure, and organizational processes to ensure that information technology is utilized as optimally as possible. Information technology governance has a broader scope and concentrates on the performance and the transformation of information technology to meet the needs of today, and that will come from both internal and external [3]. The purpose of this study was to determine the extent to which the UPT the computer applying the COBIT 4.1 Framework and already to where Maturity Level. This research using quantitative and qualitative data methods was taken through literature studies, field studies, interviews, observation, and questionnaires. Then the data obtained from interviews and questionnaires will be assessed and processed to become information. The following domain and the process that had the author previously specified, namely the domain Monitor and Evaluate & Deliver and Support. For the domain Monitor and Evaluate, the authors use the process of Monitor and Evaluate IT Performance & Provide IT Governance while the domain Deliver and Support the author using the process of Define and manage Service Levels & Manage problem.